Biodiversity conservation of coastal fish of Indonesia - Victor P. H. Nikijuluw (Jurnal Iktiologi Indonesia, 2018)
Each species has a special value. No species was created without intention. If one species matters, all species are altogether admirably important. This paper elucidates critical importance of species conservation in the context marine fish biodiversity in Indonesia. This resource endowment has not been truly known and hence improperly utilized. As direct consequences, biodiversity loss and species extinction are unstoppable trend. This condition is attributed to the lack systematic research and serious education programs. Beside the needs of improving research and education at national level, conservation programs should be intentionally adapted by regional government. Of the various available conservation approaches, the adapting of focal species by each regional government may become an effective approach to massively promote fish conservation program at provincial and regency levels. It also may become an input for conservation practices at larger scale. Abstrak Setiap spesies mempunyai nilai khusus. Tidak ada satu spesies pun yang diciptakan tanpa tujuan. Jika satu spesies saja begitu berarti, keberadaan semua spesies sekaligus sangat penting. Makalah ini menekankan begitu pentingnya konser-vasi spesies pada keragaman hayati laut di Indonesia. Sumber daya ini belum diketahui dengan sempurna dan sebab itu menjadi alasan untuk tidak dimanfaatkan dengan baik. Sebagai akibatnya, kehilangan keragaman hayati dan kepunahan spesies adalah kecenderungan yang tidak terhentikan. Hal ini terjadi karena kekurangan penelitian dan program pendi-didikan. Selain kebutuhan untuk meningkatkan penelitian dan pendidikan pada skala nasional, program konservasi harus sengaja diadakan di tingkat daerah. Dari berbagai pendekatan program konservasi, penentuan spesies kunci bisa menjadi pendekatan efektif untuk mempromosikan konservasi spesies ikan secara masif oleh pemerintah daerah provin-si atau kabupaten. Pendekatan ini bisa menjadi pelajaran bagi praktif konservasi pada skala yang lebih luas.